2021
DOI: 10.1530/erc-20-0436
|View full text |Cite
|
Sign up to set email alerts
|

Targeting EML4-ALK gene fusion variant 3 in thyroid cancer

Abstract: Finding targetable gene fusions can expand the limited treatment options in radioactive iodine-refractory (RAI-r) thyroid cancer. To that end, we established a novel cell line ‘JVE404’ derived from an advanced RAI-r papillary thyroid cancer (PTC) patient, harboring an EML4-ALK gene fusion variant 3 (v3). Different EML4-ALK gene fusions can have different clinical repercussions. JVE404 cells were evaluated for cell viability and cell signaling in response to ALK inhibitors crizotinib, ceritinib and lorlatinib, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…With lorlatinib, the patient achieved ongoing PR after seven months of therapy. The study showed that lorlatinib was more efficient than the already administered crizotinib in vivo and in vitro [ 155 ].…”
Section: Targeting Gene Fusions In Differentiated Thyroid Cancermentioning
confidence: 99%
“…With lorlatinib, the patient achieved ongoing PR after seven months of therapy. The study showed that lorlatinib was more efficient than the already administered crizotinib in vivo and in vitro [ 155 ].…”
Section: Targeting Gene Fusions In Differentiated Thyroid Cancermentioning
confidence: 99%
“…Aydemirli et al. reported a partial response in an EML-ALK fusion patient treated with lorlatinib after resistance to crizotinib ( 7 ). de Salins et al.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is classified into two histological groups: SCLC (~17.3%) and NSCLC (~82.7%) (46)(47)(48), of which lung adenocarcinoma and lung squamous cell carcinoma are the major subgroups (48). Since the EML4-ALK fusion gene was discovered in lung adenocarcinoma in 2007, it has been considered to be a characteristic gene of lung cancer; however, in recent years, it has gradually been detected in other types of cancer, such as thyroid cancer, gastric stromal tumors and leiomyoma (11,(49)(50)(51). According to a previous study, the oncogenic fusion of EML4-ALK is present in 3-5% of NSCLC (27).…”
Section: Clinical Features Of Eml4-alk In Nsclcmentioning
confidence: 99%